2017
DOI: 10.3892/mmr.2017.8160
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 inhibition sensitizes tamoxifen‑resistant breast cancer cells through cell cycle regulation

Abstract: Enhancer of zeste homologue 2 (EZH2), a catalytic subunit of polycomb repressive complex 2, is overexpressed in a number of different tumors including breast cancer, and serves important roles in cell cycle regulation, proliferation, apoptosis, tumorigenesis and drug resistance. However, it remains unclear whether EZH2 contributes to tamoxifen resistance in breast cancer. In the present study, the role of EZH2 in tamoxifen resistance in MCF‑7 cells was investigated. EZH2 was overexpressed in MCF‑7 tamoxifen‑re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Moreover, EZH2 is involved in various physiological or pathological processes, most of which are achieved through the regulation of cell growth, proliferation, senescence, or apoptosis [ 29 32 ]. Consistently, prior research discovered that EZH2 knockdown resulted in repression of cell proliferation and cell cycle entry in breast cancer, accompanied by a decline in cyclin D1 expression [ 33 ]. Also, EZH2 inhibition resulted in the subsequent reduction in myeloma cell proliferation and an increase in cell cycle entry [ 34 ].…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, EZH2 is involved in various physiological or pathological processes, most of which are achieved through the regulation of cell growth, proliferation, senescence, or apoptosis [ 29 32 ]. Consistently, prior research discovered that EZH2 knockdown resulted in repression of cell proliferation and cell cycle entry in breast cancer, accompanied by a decline in cyclin D1 expression [ 33 ]. Also, EZH2 inhibition resulted in the subsequent reduction in myeloma cell proliferation and an increase in cell cycle entry [ 34 ].…”
Section: Discussionsupporting
confidence: 59%
“…Over the last decade, researchers put efforts to illuminate the complex network of ER transcriptional effects such as ER/ERK/MAPK pathway and stress-activated protein kinase/c-junNH2 terminal kinase pathway and suggested that alterations of the elements in these signaling pathway play an important role in resistance to tamoxifen in breast cancer treatment. 28 30 Moreover, with the development of molecular research, several critical importance targets of breast cancer cells have been identified, such as HER2, other receptor tyrosine kinases, and components of the PI3K/AKT/mTOR and Raf/MEK/ERK pathways. 31 , 32 In the current study, H19 overexpression may be related to the poor prognosis of tamoxifen-resistance breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SASP gene-upregulation by PRC2 inhibition is independent of p16 CDKN2A/p16 was considered a critical PRC2 target for proliferation blockage upon PRC2 inhibition in many cancers including nasopharyngeal carcer, breast cancer, leukemia, and ovarian cancer [44][45][46][47]. However, the requirement of p16 in these circumstances has not been studied yet.…”
Section: Prc2 Inhibition Induces Multiple Features Of Cellular Senesc...mentioning
confidence: 99%